From religious emotions to affects: historical and theoretical reflections on injury to feeling, self and religion. Issue 2 (3rd April 2019) - Ural, N. Yasemin; Berg, Anna Lea
ABSTRACT: Images of angry Muslims have become a common sight in repeated controversies problematising the compatibility of Islam and freedom of speech. To explain such outrage, it is often put forward that Muslims reacted to the disrespect and violation of their 'religious feelings'. In this paper, we challenge the trope of hurt religious feelings in the explanation of unrest. Referring to the writings of Schleiermacher, James and Taylor, the discussion traces how religion and feeling have become inextricably intertwined, located within the individual self and institutionalised as a dominant interpretation of religion. We introduce affect as a conceptual alternative to such understandings, which allows us to analyse the emphasis on Muslim emotionality as a relationship between Muslim and secular bodies, hence no longer reduced to the interiority of Muslim subjects. We will illustrate the potential of an affect-based approach discussing Muslim feelings' vital role in the construction of European democracies.